Ultra-low-head hydroelectric technology: A review. (October 2017) - Zhou, Daqing; Deng, Zhiqun (Daniel)
Abstract: In recent years, distributed renewable energy-generation technologies, such as wind and solar, have developed rapidly. Nevertheless, the utilization of ultra-low-head (ULH) water energy (i.e., situations where the hydraulic head is less than 3 m or the water flow is more than 0.5 m/s with zero head) has received little attention. We believe that, through technological innovations and cost reductions, ULH hydropower has the potential to become an attractive, renewable, and sustainable resource. This paper investigates potential sites for ULH energy resources, the selection of relevant turbines and generators, simplification of civil works, and project costs. This review introduces the current achievements on ULH hydroelectric technology to stimulate discussions and participation of stakeholders to develop related technologies for further expanding its utilization as an important form of renewable energy.